2015
DOI: 10.1016/j.ajps.2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal delivery of fluorescein isothiocyanate-dextrans using the combination of microneedles and low-frequency sonophoresis

Abstract: This study aimed to evaluate the patient-friendly methods that are used in the delivery of hydrophilic macromolecules into deep skin layers, in particular, the combination of microneedles patch (MNs patch) and low-frequency sonophoresis (SN). The hydrophilic macromolecule drug fluorescein isothiocyanate (FITC)-dextrans (FD-4: MW 4.4 kDa) was used as the model drug in our experimental design. In this study, excised porcine skin was used to investigate and optimize the key parameters that determine effective MNs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Research by Pamornpathomkul et al 44 examined the effects of combining low-frequency SP with microneedles in the in vitro transdermal delivery of fluorescein isothiocyanate-dextrans. By using confocal laser scanning microscopy, they determined that the magnitude of fluorescence was greatest when the two transdermal drug delivery techniques were combined, when compared with using each method individually.…”
Section: Combining Transdermal Drug Delivery Techniquesmentioning
confidence: 99%
“…Research by Pamornpathomkul et al 44 examined the effects of combining low-frequency SP with microneedles in the in vitro transdermal delivery of fluorescein isothiocyanate-dextrans. By using confocal laser scanning microscopy, they determined that the magnitude of fluorescence was greatest when the two transdermal drug delivery techniques were combined, when compared with using each method individually.…”
Section: Combining Transdermal Drug Delivery Techniquesmentioning
confidence: 99%
“…The in vitro permeation experiment demonstrated that the extent of permeation was greater for the combination of microneedles and sonophoresis than for each method alone. 98 Manikkath et al aimed to evaluate the individual and collective impacts of peptide dendrimers and low-frequency ultrasound on the permeability of transdermally administered ketoprofen. The results of the study indicated that combining peptide dendrimer treatment with ultrasound application exhibited enhancement ratios of up to 1369.15.…”
Section: Recent Advances In Physical Methods Of Permeation Enhancemen...mentioning
confidence: 99%
“…The microneedle system provides some advantages: i) site-specific delivery with exact penetration depth ii) painless drug delivery with a high flow rate of drug iii) minimal skin damage with the flexibility of uses at any time. To ensure a high output delivery Pamornpathomkul et al [99] tested the combined effects of low-frequency SP with microneedles in vitro TDD of fluorescein isothiocyanate dextrans (FSD). The result showed the greatest delivery at combined technique rather than individual method.…”
Section: Electroporationmentioning
confidence: 99%